MULTIMODAL DISCOURSE ANALYSIS OF HUMOR AND SARCASM ON “EMOTIONAL DAMAGE” VIDEO FOOTAGE MEMES - Reksha Ramdani Azzahra; Budi Eko Pranoto (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2023)
This study aims to reveal the existence of the sense of sarcastic humour that is hidden in some visual data in the form of semiotic and verbal data in the form of transcriptions that have been selected from several video data. The approach used in this analysis is using Multimodal Discourse Analysis (MDA) and combined with theory from The Language Metafunction. The results found are in the form of three interpretation results generated from video data, in the form of insult, satire, and dark humour. Based on these three results, it is revealed that there is an underlying purpose, making the sarcastic humour of the “Emotional Damage” meme a bridge between ironic and non-ironic humour. The research contributes to a deeper understanding of contemporary communication nuances and the multifarious dimensions of humour and sarcasm.Keywords: humour, language metafunction, MDA, sarcastic humour